Correction: Computational capabilities of a multicellular reservoir computing system. - Vladimir Nikolić; Moriah Echlin; Boris Aguilar; Ilya Shmulevich (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0282122.].